(untitled) (International Journal of Innovative Technologies in Economy, 2024)
This systematic literature review investigates the integration of TikTok in secondary Business Studies education across South African schools, focusing on implementation practices and educational outcomes. As social media platforms continue to reshape educational practices globally, the study employs the Technology Acceptance Model as a theoretical framework to understand the impact of TikTok integration on Business Studies teaching and learning in South African contexts. Through a comprehensive analysis of existing research, this study synthesizes critical findings regarding the adoption, effectiveness, and outcomes of TikTok-based educational initiatives in secondary Business Studies classrooms. The review explores various dimensions, including platform integration strategies, pedagogical innovations, student engagement patterns, teacher development needs, and content creation approaches. Additionally, it identifies implementation challenges and opportunities associated with TikTok-based learning and highlights implications for teaching practice, educational policy, and future research in the South African secondary education sector. By synthesizing insights from diverse scholarly works, this review offers valuable perspectives for educators and administrators aiming to navigate the complexities of social media integration in Business Studies education within the South African context.